The Experience of Using Cryotechnology in Animal Breeding to Ensure Food Security in Ukraine - Bogdaniuk, Anastasiia; Petrushko, Maryna; Garkavii, Volodymyr (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):294